Development and Application of Mass Spectroscopy Assays for Nε-(1-Carboxymethyl)-L-Lysine and Pentosidine in Renal Failure and Diabetes. (8th February 2020) - O'Grady, Katherine L; Khosla, Sundeep; Farr, Joshua N; Bondar, Olga P; Atkinson, Elizabeth J; Achenbach, Sara J; Eckhardt, Brittany A; Thicke, Brianne S; Tweed, Amanda J; Volkman, Tammie L; Drake, Matthew T; Hines, Jolaine M; et al.
Abstract: Background: Advanced glycation end products (AGEs) are formed via the nonenzymatic glycation of sugars with amino acids. Two AGEs, N ε -(1-carboxymethyl)-L-Lysine (CML) and pentosidine, have been observed to be elevated in subjects suffering from a multitude of chronic disease states, and accumulation of these compounds may be related to the pathophysiology of disease progression and aging. Methods: We describe here the development and validation of a specific and reproducible LC-MS/MS method to quantify CML and pentosidine in human serum with lower limits of quantitation of 75 ng/mL and 5 ng/mL, respectively. The analyte calibration curve exhibited excellent linearity at a range of 0–10 900 ng/mL for CML and 0–800 ng/mL for pentosidine. High-low linearity of 5 serum pairs was assessed, with a mean recovery of 103% (range 94—116%) for CML, and 104% (range 97—116%) for pentosidine. Results: Serum concentrations of CML and pentosidine were quantified in 30 control and 30 subjects with chronic renal insufficiency. A significant increase in both analytes was observed in renal failure compared to control subjects (2.1-fold and 8.4-fold, respectively; P  < 0.001 for both). In a separate cohort of 49 control versus 95 subjects with type 2 diabetes mellitus (T2DM), serum CML but not serum pentosidine, was significantly elevated in the T2DM patients, and CML was also correlated with glycemic control, as assessed by hemoglobin A1c ( r  = 0.34, P  < 0.001). Conclusions: These mass spectroscopy-based assays for serum CML and pentosidine should be useful in accurately evaluating circulating levels of these key AGEs in various disease states.